Pengembangan Media Video Animasi Berbasis Aplikasi Powtoon Pada Tema 7 Subtema 2 di Kelas V SDN 101610 Purbabangun T.A 2022/2023 - Harahap, Ade Yulis; Simanungkalit, Erlinda; Sembiring, Masta Marselina; Mailani, Elvi; Rozi, Fahrur; Faisal, Faisal; Handayani, Dila (Journal of Student Development Information System (JoSDIS), 2023)
This research is motivated by the use of media in the learning process that is less skilled and creative and only uses makeshift media. This study aims to produce a valid, practical and effective powtoon-based animated video media in supporting learning success. This research is research and development using the 4D development model (define, design, development and dissemination). The subjects of this study were fifth grade students at SD Negeri 101610 Purbabangun and the object of this research was the animated video media based on the powtoon application. The results showed that the validation by material experts in stage I before revision obtained a percentage of 56.9% in the "Quite Adequate" category with revisions, then in stage II it obtained a percentage of 89.2% in the "Very Eligible" category without revisions and the design validation results obtained a percentage of 85 .3% in the category “Very Eligible. Practical tests by educational practitioners get a percentage of 91.7% "Very Practical". The results of the media effectiveness test through the pre-test obtained an average of 40.42% with the "Not Complete" completeness criteria while in the post-test obtained an average of 88.125 with the "Completed" completeness criteria. It can be concluded that the product being developed is very feasible, practical and effective for use in learning in elementary schools.